Effect of replacing synthetic nitrogen fertilizer with animal manure on grain yield and nitrogen use efficiency in China: a meta‐analysis - Ren, Keyu; Sun, Yue; Zou, Hongqin; Li, Dejin; Lu, Changai; Duan, Yinghua; Zhang, Wenju (Frontiers in Plant Science, 2023)
Substituting synthetic nitrogen (N) fertilizer with manure is an effective method to reduce reliance on synthetic N fertilizer and sustain food production. However, the effects of manure substitution on crop yield and nitrogen use efficiency (NUE) are still uncertainties under varying fertilization management practices, climate conditions, and soil properties. Here, we conducted a meta-analysis of wheat, maize, and rice based on 118 published studies conducted in China. The results indicated that overall, substituting synthetic N fertilizer with manure increased yield by 3.33.9% for the three grain crops, and increased NUE by 6.310.0%. Crop yields and NUE did not significantly increase at low N application rate ( 120 kg hm-2) or high substitution rate (> 60%). Yields and NUE values had higher increases for upland crops (wheat and maize) in temperate monsoon climate/temperate continental climate regions with less average annual rainfall (AAR) and lower mean annual temperature (MAT), while rice had higher increases in subtropical monsoon climate regions with more AAR and higher MAT. The effect of manure substitution was better in soil with low organic matter and available phosphorus. Our study shows that the optimal substitution rate was 44% and the total N fertilizer input cannot be less than 161 kg hm-2 when substituting synthetic N fertilizer with manure. Moreover, site‐specific conditions should also be considered.